Efficacy of Peer Networks to Increase Social Connections Among High School Students With and Without Autism Spectrum Disorder. (October 2015) - Hochman, Julia M.; Carter, Erik W.; Bottema-Beutel, Kristen; Harvey, Michelle N.; Gustafson, Jenny R.
Although peer interaction takes on increased salience during adolescence, such social connections remain elusive for many high school students with autism spectrum disorder (ASD). This social isolation can be particularly prevalent within unstructured school contexts. In this study, we examined the effects of a lunchtime peer network intervention on the social engagement and peer interactions of four adolescent students with ASD. Upon introduction of the peer networks, we observed substantial increases in the percentage of intervals containing peer interactions and social engagement across all participants. Further, students with ASD, peer partners, and school personnel all considered the intervention to be acceptable and feasible. We offer recommendations for research and practice aimed at enhancing the efficacy and social validity of peer-mediated interventions at the secondary school level.